(untitled) - Blofeld, John (London, 1965)
The I Ching, probably the oldest book in existence, provides a system of knowledge that makes it possible to analyze the patterns of changes in life governed by the Immutable Law of Change. Whether we use the I Ching for divination or to study the principles involved with it, if we allow ourselves to be governed by its teachings, we shall enrich the content of our lives, free ourselves from anxiety, and become harmless or even intelligently helpful to others and pleasant companions to ourselves.
Keywords: Philosophy, Chinese,Triết học Trung Quốc